Electrochemical stability and corrosion resistance of Ti-Mo alloys for biomedical applications - Oliveira, N. T. C. [UNESP]; Guastaldi, Antonio Carlos [UNESP] (Elsevier B.V., 2009)
Electrochemical behavior of pure Ti and Ti-Mo alloys (6-20 wt.% Mo) was investigated as a function of immersion time in electrolyte simulating physiological media. Open-circuit potential values indicated that all Ti-Mo alloys studied and pure Ti undergo spontaneous passivation due to spontaneously formed oxide film passivating the metallic surface, in the chloride-containing solution. It also indicated that the addition of Mo to pure Ti up to 15 wt.% seems to improve the protection characteristics of its spontaneous oxides. Electrochemical impedance spectroscopy (EIS) studies showed high impedance values for all samples, increasing with immersion time, indicating an improvement in corrosion resistance of the spontaneous oxide film. The fit obtained suggests a single passive film present on the metals' surface, improving their resistance with immersion time, presenting the highest values to Ti-15Mo alloy. Potentiodynamic polarization showed a typical valve-metal behavior, with anodic formation of barrier-type oxide films, without pitting corrosion, even in chloride-containing solution. In all cases, the passive current values were quite small, and decrease after 360 h of immersion. All these electrochemical results suggest that the Ti-15Mo alloy is a promising material for orthopedic devices, since electrochemical stability is directly associated with biocompatibility and is a necessary condition for applying a material as biomaterial. (C) 2008 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Ti-Mo alloys; Corrosion resistance; Biocompatible alloys; Titanium alloys